PENGARUH KUALITAS PRODUK, KELENGKAPAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT INTERNATIONAL HARDWARE INDO DI KOTA BATAM - learns, micheal; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2021)
In the current era of globalization, company development is caused by changes in the human mindset that are increasingly dynamic. Market activity is needed by companies to seek profit. In this study conducted research on the effect of product quality, product completeness and promotion on purchasing decisions at PT International Hardware Indo in Batam City. The method used to research is quantitative method and its collection uses a google form questionnaire. The sample was obtained as 144 samples. This study is using simple random sampling. The study used SPSS version 25. The results in the research on product quality were 2,025> 1,977 and sig 0.045 <0.05. This means that product quality has positive and significant effect on purchasing decisions. product completeness were -0.195 <1.977 and sig 0.846> 0.05, which means product completeness has negative and does not significant effect on purchasing decisions. And promotion were 8,135> 1,977 and sig 0,000 <0.05 means that promotion has positive and significant effect on purchasing decisions. The result f results value of 34.867 > 2.67, which means simultaneously product quality, product completeness and promotion have a significant effect on purchasing decisions.